The relationship between sleep and menstrual problems in early adolescent girls - Orsolya Kiss; Anne Arnold; Helen A. Weiss; Fiona C. Baker (Sleep Science and Practice)
Abstract Introduction Adolescence is marked by hormonal, physical, neural, and behavioral changes, including in sleep patterns and, in females, the onset of menarche. Menstrual problems, such as painful menses, are common and contribute to school absences, and could indicate gynecological conditions impacting reproductive health. While studies in adults have shown associations between sleep disturbances and menstrual problems, this relationship is less understood in adolescents. Our study explores the association between sleep, menstrual problems, and menarche in a diverse sample of early adolescent girls in the U.S. Methods We used linear mixed-effect models to analyze associations between sleep behavior (self- and caregiver-reported) and menstrual problems (self-reported cycle irregularity, premenstrual symptom and menstrual pain severity and their impact on daily life) and menstrual characteristics (menstrual flow) in 3,037 post-menarcheal adolescent girls (Mean age:13.03 years) from the ABCD Study®. Covariates included years since menarche, race, ethnicity, parental education, and body mass index. We also used longitudinal data to explore changes in sleep behavior as a function of menarche. Results Of the sample, 26.2% reported moderate-severe premenstrual symptoms and 20.8% reported moderate-severe menstrual pain. 23.3% reported irregular menstrual cycles, 15.9% reported heavy menstrual flow. Shorter sleep duration was associated with greater menstrual pain intensity (β =—0.19) and impact on daily activities (β = -0.15), irregular cycles (β = -0.17), and severe premenstrual symptoms (β = -0.04). Higher sleep disturbance scores correlated with greater menstrual pain (β = 0.18) and premenstrual symptom severity (β = 0.03). Later wake-up times were linked to greater menstrual pain intensity (β = 0.14). Shorter time since menarche was associated with lower menstrual flow (β = 0.07) and pain intensity (β = 0.51) and less severe premenstrual symptoms (β = 0.07). Being post-menarche was associated with later bedtimes and shorter sleep duration. Conclusion Findings of links between sleep behavior and menstrual problems in early adolescence underscore the importance of addressing sleep and menstrual issues in healthcare screenings and educational initiatives for adolescents. Future research should focus on longitudinal and intervention studies to clarify these relationships.